2013
DOI: 10.5586/asbp.2013.028
|View full text |Cite
|
Sign up to set email alerts
|

Content of pyrrolizidine alkaloids in the leaves of coltsfoot (Tussilago farfara L.) in Poland

Abstract: Coltsfoot (<em>Tussilago farfara</em> L.) is a common species, widely used in European and Chinese traditional medicine for the treatment of respiratory diseases. However, raw material from this plant contains hepatotoxic pyrrolizidine alkaloids (PAs). The aim of the study was to determine the variability of the level of PAs (senkirkine and senecionine) in leaves of coltsfoot originated from natural populations in Poland. In the phytochemical analysis, 20 samples of <em>T. farfara</em> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
14
0
2
Order By: Relevance
“…Due to the presence of PA in several species relevant for human and animal nutrition, they may pose a threat to human health through their presence in herbal teas, herbal medicines, dietary supplements, vegetables, cereals, wheat grain, honey and pollen [ 93 , 94 , 95 , 96 , 97 , 98 ]. Cases of intoxication by contaminated cereals, teas, and salads have been extensively reported [ 97 , 99 , 100 ].…”
Section: Human and Animal Consumption Of Pamentioning
confidence: 99%
“…Due to the presence of PA in several species relevant for human and animal nutrition, they may pose a threat to human health through their presence in herbal teas, herbal medicines, dietary supplements, vegetables, cereals, wheat grain, honey and pollen [ 93 , 94 , 95 , 96 , 97 , 98 ]. Cases of intoxication by contaminated cereals, teas, and salads have been extensively reported [ 97 , 99 , 100 ].…”
Section: Human and Animal Consumption Of Pamentioning
confidence: 99%
“…In Norway, the dried and cut leaves of coltsfoot, as folk medicines, are sold and used in teas for the relief of coughs and chest complaints ( Xue et al , 2012 ). In Europe, the leaves are used to treat bronchial infections while in China the flower buds are preferred ( Adamczak et al , 2013 ). Moreover, in traditional Chinese medicines (TCMs), the flower bud of coltsfoot is often used the form of processed honey-fry, which showed a detoxifying effect.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them have been deemed to possess biological activities, and this is notably the case with TSL ( 13 ). Most notably, the concentration of PAs in coltsfoot varies widely ( Adamczak et al , 2013 ) and cultivation of a PAs-free variety is being developed in Austria, ( Wawrosch et al , 2000 ). Moreover, Pfeiffer et al (2008) highlights the correlation of vegetative multiplication in coltsfoot, as an important pioneer species, which has been achieved rapidly via repeated clonal growth and subsequent clonal reproduction ( Pfeiffer et al , 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the data are widely ranging from 0 to 368 mg/g. [33,36] For 20 natural populations from Poland, Adamczak et al [33] reported (senkirkine and senecionine) content in the range of 0.06À1.04 mg/g. According to these data, PAs, found in the studied Bulgarian population of T. farfara, were close to the lower range limit and could be perceived as population with low alkaloid content.…”
mentioning
confidence: 98%
“…Factors that affect the accumulation of alkaloids are still under discussion, but it is outlined that variability of PAs is mainly genetically determined and it can be increased by environmental factors. [33] The presence of the double bond is an important determinant in the hepatotoxicity of PAs, because only those with 1,2-unsaturation are hepatotoxic. The toxicity of PAs is due to metabolic activation.…”
mentioning
confidence: 99%